Protection of Traditional Knowledge: Finding an Appropriate Legal Framework for Bangladesh - Islam, Mohammad Towhidul; Zaman, Moniruz (Dhaka University Law Journal, 2021)
Abstract not available Dhaka University Law Journal, Vol. 31, 2020 P.29-48